2022
DOI: 10.1002/jso.26793
|View full text |Cite
|
Sign up to set email alerts
|

Body composition predictors of mortality in patients undergoing surgery for long bone metastases

Abstract: Background and Objectives Body composition measurements using computed tomography (CT) may serve as imaging biomarkers of survival in patients with and without cancer. This study assesses whether body composition measurements obtained on abdominal CTs are independently associated with 90‐day and 1‐year mortality in patients with long‐bone metastases undergoing surgery. Methods This single institutional retrospective study included 212 patients who had undergone surgery for long‐bone metastases and had a CT of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
3
6
0
Order By: Relevance
“…These observations were consistent with a recent study by Groot et al. that found decreased PMA on CT was associated with a higher likelihood of mortality at 1 year (Hazard ratio, HR, 1.68; 95% CI, 1.08–2.61; p = 0.02) in 212 patients undergoing surgery for extremity metastases 28 . Although the authors concluded body composition measurements could be used as a novel imaging biomarker to supplement current survival prediction tools for patients with long‐bone metastases, they did not further analyze if predictions made by these tools could actually be improved when morphometric factors were considered.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These observations were consistent with a recent study by Groot et al. that found decreased PMA on CT was associated with a higher likelihood of mortality at 1 year (Hazard ratio, HR, 1.68; 95% CI, 1.08–2.61; p = 0.02) in 212 patients undergoing surgery for extremity metastases 28 . Although the authors concluded body composition measurements could be used as a novel imaging biomarker to supplement current survival prediction tools for patients with long‐bone metastases, they did not further analyze if predictions made by these tools could actually be improved when morphometric factors were considered.…”
Section: Discussionsupporting
confidence: 93%
“…[17][18][19][20][21][22][23]25 These observations were consistent with a recent study by Groot et al that found decreased PMA on CT was associated with a higher likelihood of mortality at 1 year (Hazard ratio, HR, 1.68; 95% CI, 1.08-2.61; p = 0.02) in 212 patients undergoing surgery for extremity metastases. 28 Although the authors concluded body composition measurements could be used as a novel imaging biomarker to supplement current survival prediction tools for patients with long-bone metastases, they did not further analyze if predictions made by these tools could actually be improved when morphometric factors were considered. Our study demonstrated that decreased PMA was still associated with higher 90-day and 1-year mortality after controlling for the predictions made by three extensively validated SPAs, implying that body composition metrics might capture some prognostic value not currently appreciated by these algorithms.…”
Section: Unadjustedmentioning
confidence: 99%
“…In the entire cohort, 36.63% (43,305/118,227) of patients experienced early death. Other studies reported that the 3-month mortality rate was approximately 30% [ 30 - 32 ], which was consistent with this study. According to variables’ importance, this study found that chemotherapy, primary site, and liver metastasis were the top 3 important variables associated with early death.…”
Section: Discussionsupporting
confidence: 93%
“…Predictive models and clinical risk assessment tools continue to be an area of active research in metastatic bone disease 67,[73][74][75][76] . The Skeletal Oncology Research Group (SORG) machinelearning (ML) algorithms have been widely studied as tools to estimate survival in patients with extremity metastases.…”
Section: Predictive Modelsmentioning
confidence: 99%
“…Table III shows some recent studies evaluating patients with metastatic bone disease [66][67][68][69][70][71][72][73][74][75][76] .…”
Section: Metastatic Bone Tumorsmentioning
confidence: 99%